Percutaneous closure of subclavian iatrogenic injuries after central venous catheterization: a Latin American experience - Rey Chaves, Carlos Eduardo; Orozco, Claudia; Posada, Eduardo; Gómez Zuleta, María; Fajardo, Ernesto; Barón, Vladimir; Hernández Rodríguez, Oscar Geovanny (Frontiers in Surgery, 2023)
Introduction Arterial injuries following central venous catheterization (CVC) range between 0.1%–2.7%. The open surgical approach could be related to increased rates of morbidity and mortality. Vascular closure devices (VCD) are often used for the management of these patients with a success rate of up to 80%. Objectives Describe our experience in managing arterial vascular injuries following central venous catheterization with Perclose ProGlide (Abbott Vascular IncSanta Clara, CA, USA). Methods A retrospective review of all patients over 18 years old who underwent percutaneous closure of arterial injuries following central venous catheterization in our center between January 2018 and May 2023 was included and reported with a 90-day follow-up. Results 3 Patients were included, in all cases, access to the CVC were right with a subclavian artery injury. Ultrasound and fluoroscopy guide was used in all cases. For the 3 cases, a percutaneous technique using Perclose ProGlide (Abbott Vascular IncSanta Clara, CA, USA) was performed. With a 100% success rate, and no complications evidenced after 90 days of follow-up. Conclusion Inadvertent arterial catheterization it's a non-negligible complication after CVC placement. VCD could be considered a safe and feasible approach for the management of these traumatic injuries.